An Improved Directional Broadcast Algorithm Based on Brownian Motion. (24th July 2014) - Li, Shibao; Lou, Linlin; Wang, Yu; Sun, Lu; Hong, Li
Several broadcast algorithms have been developed in recent years. However, the problem of reducing routing overhead in ad hoc networks is always to be concerned. This paper proposes an improved directional broadcast algorithm based on Brownian motion for AODV protocol (DBB-AODV). We bring Brownian motion into network model and gain the distribution of the nodes which encountered destination before. This algorithm uses encounter records to predict the direction to destination and forwards RREQ packets with reasonable probability according to the distribution just mentioned. Simulation results indicate that DBB-AODV saves up to 20% of average routing overhead compared to the probabilistic protocol and about 80% of the blind flooding.